Educational Networks, Mutual Fund Voting Patterns, and CEO Compensation - Butler, Alexander W.; Gurun, Umit G. (Review of Financial Studies, 2012)
Mutual funds whose managers are in the same educational network as the firm's CEO are more likely to vote against shareholder-initiated proposals to limit executive compensation than out-of-network funds are. This voting propensity is stronger when voting among the funds in a family is not unanimous. Furthermore, CEOs of firms who have relatively high levels of educationally connected mutual fund ownership have higher levels of compensation than their unconnected counterparts. This aspect of executive compensation is related to both the abnormal trading performance of the connected investors in the firm and the perceived quality of firm management by the connected investors.